Tourism Destination Based on Local Values in Wonosoco Village, Kudus Regency, Indonesia - Fatmawati, Noor; Prasetya, Aditya Isnaini (University of Merdeka Malang, 2021)
Wonosoco Village has natural and cultural phenomena based on local wisdom that have the potential as a tourist destination. However, the lack of understanding of the village community in developing tourism potential as well as the geographical conditions of the village which are prone to landslides and flash floods, it is difficult to be promoted to become a tourist village, so the community does not understand the essence of the values of village local wisdom. The purpose of this study is to analyze tourist destinations based on local wisdom values in Wonosoco Village, Kudus Regency. The qualitative research method used is a phenomenological approach. The main informants are the village head, with informants supporting the village community, Pokdarwis members, and tourists. Retrieval of data through observation and interview techniques with data analysis using the Spradley Model through the stages of analysis of domains, taxonomies, components, and cultural themes. The findings show that there are potential tourist destinations, namely natural resources, human resources, recreational facilities, and events organized by the government. This tourist destination essentially has local wisdom values in the form of spiritual values, social values, and cultural values that can construct knowledge for the community to be realized in everyday life, so it needs to be preserved to provide a transfer of values to generations to respect the values of wisdom. local cultureÂ DOI:https://doi.org/10.26905/lw.v13i1.4723